EVALUATION OF RADIO PATH PARAMETERS OF INFOCOMMUNICATION SYSTEMS 5G/6G - VASYLKIVSKYI, Mykola; KOLOMIETS, Alyona; BUDASH, Mykhailo (Herald of Khmelnytskyi National University. Technical sciences, 2022)
A study of the parameters of the radio path was carried out to substantiate the possibility of expanding the integrated multi-level spectrum of 5G/6G and increasing the efficiency of the station equipment of the next generation information communication systems. The paper presents the results of research into the bandwidth of the transmission channel in the THz range, taking into account the transmission power and noise of the components of modern telecommunication systems, as well as the influence of atmospheric attenuation. The idea of ​​a new spectrum, possibilities and problems of using the THz range for both communication and scanning were presented. It also describes the process of modeling and measuring new channels along high-frequency bands, for scenarios with large aperture arrays, non-terrestrial networks, and scanning in millimeter and THz bands. Improved methods for solving technical problems identified in 5G systems, such as mobility and coverage, as well as implementation problems of telecommunications equipment, are identified. In particular, to facilitate the optimal design of radio technologies in 6G systems, it is necessary to model transmission channels with higher accuracy. In addition, to improve the transmission characteristics of millimeter waves, improvements are needed in the radio signal beamforming technology, in particular in beamforming during the scanning process. It is determined that the use of the millimeter range spectrum will be significantly improved due to the improvement of technologies related to materials, radio frequency components and signal processing. Thus, it becomes possible to achieve ultra-high data transfer speed and high-precision scanning resolution. A study of the theoretical foundations of the creation of new devices, the design of electronic, photonic and hybrid receivers, large-sized antenna arrays, gratings on a common crystal or case, and new technologies for the formation of materials for the manufacture of gratings, which ensure the rapid development of communication technologies in the THz range, was carried out. time identified the need for further research in the field of designing powerful high-frequency devices, new materials for antennas and RF transistors, receiver architecture, channel modeling, grating signal processing, and energy efficiency issues. The 6G radio path has been studied, which will contain new capabilities and provide new services using new wireless technologies. It is determined that the 6G system will include many new elements, such as new spectrum, new channels, new materials, new antennas, new computing technologies and new end devices. THz spectrometry at 6G has been found to have many potential applications in health care, industry, food quality control, and the environment, as the vibrational and rotational frequencies of most molecules lie in the THz range. THz spectrometry is of considerable interest due to its ability to provide continuous real-time information through dynamic, non-invasive, passive and non-contact measurements. Of particular note is that THz spectrometry provides results comparable to professional CT or MRI machines, but with a much safer and more portable functional process.